Changes of RNA N6-methyladenosine in the hormesis effect induced by arsenite on human keratinocyte cells. (April 2019) - Chen, Hongyu; Zhao, Tianhe; Sun, Donglei; Wu, Mei; Zhang, Zunzhen
Abstract: Arsenite exposure can induce a biphasic response called "hormesis", and oxidative stress has been proposed to play critical roles in the hormesis effect. However, the precise mechanisms underlying the hormesis effect induced by arsenite is largely unknown. Recently, N 6 -methyladenosine (m 6 A) modification has been implicated to play an important role in the biological processes of cells. Nevertheless, whether and how m 6 A is involved in the hormesis of cell growth and death caused by arsenite via oxidative stress have remained a mystery. Here, oxidative stress and m 6 A as well as its methyltransferases/demethylase of human keratinocyte cells after low/high doses of arsenite exposure were simultaneously evaluated. Our results demonstrated that the treatment of human HaCaT cells with low levels of arsenite up-regulated m 6 A modification as well as its methyltransferases (METTL3/METTL14/WTAP) and inactivated the demethylase (FTO), exerting "protective response" against oxidative stress and promoting HaCaT cells survival. On the contrary, high doses of arsenite induced down-regulation of m 6 A level and enhanced oxidative stress, showing "inhibitive effects" on cell viability in HaCaT cells. Our results suggest that the reversible m 6 A modification is associated with the arsenite-driven hormesis on cytotoxicity. Graphical abstract: Unlabelled Image Highlights: Low-dose NaAsO2 generated small amount of ROS, promoting cell survival. High-dose NaAsO2 increased cytotoxicity and oxidative stress, leading to cell death. The reversible m 6 A may involved in the NaAsO2 -induced hormesis on cytotoxicity. Low-level NaAsO2 up-regulated m 6 A and methyltransferases, inactivating demethylase. High-dose NaAsO2 down-regulated m 6 A and methyltransferases, activating demethylase.